AI IN CYBERSECURITY: ADVANCEMENTS AND CHALLENGES - Poli Reddy Reddem, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This article explores the transformative role of artificial intelligence (AI) in cybersecurity, highlighting its potential to revolutionize threat detection and mitigation in an increasingly sophisticated cyber threats era. It examines the rapid growth of AI adoption in the cybersecurity sector, driven by the rising costs of data breaches and the limitations of traditional security measures. The article delves into advanced AI-powered capabilities such as anomaly detection, malware identification, phishing prevention, behavioral analytics, and threat intelligence integration. While acknowledging AI's promising future in cybersecurity, including predictive threat intelligence and automated incident response, the article also addresses critical challenges such as data bias, explainability issues, adversarial attacks, ethical considerations, and the cybersecurity skills gap. By presenting both the advancements and obstacles in AI-driven cybersecurity, this study provides a comprehensive overview of this rapidly evolving field's current landscape and future trajectory.